The Use of Information Technology in Improving the Recruitment and Selection Process of Human Resources - Novalien Carolina Lewaherilla; Victor Ernest Huwae (Politeknik Ganesha Medan, 2023)
The effective management of human resources is a critical factor in the achievement of organizational success. The recruitment and selection of competent personnel is a crucial aspect of human resource management. The objective of this research is to conduct a comprehensive analysis of the effects of information technology implementation on enhancing the recruitment and selection procedures of human resources. It is anticipated that the outcomes of this investigation will yield a more profound comprehension of the utilization of information technology in enhancing the process of recruiting and selecting personnel resources. The primary emphasis of this research is on qualitative analysis. Data collection methods involve meticulous observation and recording of data, followed by the application of analytical techniques such as data reduction, visualization, and inference to derive insights. The study's findings indicate that the incorporation of information technology in the recruitment and selection procedures of human resources has yielded several noteworthy and beneficial outcomes. The implementation of this measure has resulted in enhanced recruitment process efficiency, accuracy, and effectiveness, alongside a reduction in administrative expenses and time consumption.